2017
DOI: 10.3389/fmicb.2017.02035
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Vibrio campbellii LMB 29 Isolated from Red Drum with Four Native Megaplasmids

Abstract: Vibrio spp. are the most common pathogens for animals reared in aquaculture. Vibrio campbellii, which is often involved in shrimp, fish and mollusks diseases, is widely distributed in the marine environment worldwide, but our knowledge about its pathogenesis and antimicrobial resistance is very limited. The existence of this knowledge gap is at least partially because that V. campbellii was originally classified as Vibrio harveyi, and the detailed information of its comparative genome analysis to other Vibrio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…In addition to V. parahaemolyticus, the T3SS1 and T3SS2 gene clusters were also found to be present in many other Vibrio species. Of these, the T3SS1 gene cluster was mainly present in several species of the harveyi clade, such as V. alginolyticus, V. harveyi, and V. campbellii (Henke and Bassler, 2004;Park et al, 2004;Zhao et al, 2010;Liu et al, 2017). This conclusion was well-supported by our data showing that all tested strains of V. parahaemolyticus, V. alginolyticus, V. harveyi, and V. campbellii in our collections possessed the T3SS1 gene cluster.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In addition to V. parahaemolyticus, the T3SS1 and T3SS2 gene clusters were also found to be present in many other Vibrio species. Of these, the T3SS1 gene cluster was mainly present in several species of the harveyi clade, such as V. alginolyticus, V. harveyi, and V. campbellii (Henke and Bassler, 2004;Park et al, 2004;Zhao et al, 2010;Liu et al, 2017). This conclusion was well-supported by our data showing that all tested strains of V. parahaemolyticus, V. alginolyticus, V. harveyi, and V. campbellii in our collections possessed the T3SS1 gene cluster.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, T3SS gene clusters (T3SS1 or T3SS2) were also found in some other Vibrio species, such as V. alginolyticus, V. harveyi, V. campbellii, Vibrio tubiashii, Vibrio mimicus, and non-O1/O139 V. cholerae (Henke and Bassler, 2004;Park et al, 2004;Dziejman et al, 2005;Okada et al, 2010;Zhao et al, 2010;Liu et al, 2017). Comparative analyses have revealed that most of these clusters are more similar to the T3SS1 of V. parahaemolyticus in gene synteny and homology and harbor identical T3SS1 backbones, including all the genes annotated to encode the basal body, the needle-like structure, and the translocator; however, the hypothetical regions (the so-called effector coding regions) located between vscL and vscU genes of T3SS1, which are supposed to encode the effectors, exhibit many differences in gene content and order among those species (Ono et al, 2006;Zhao et al, 2011;Liu et al, 2017). For example, VopR, an effector encoded by vp1683 in the V. parahaemolyticus strain RIMD2210633, which is involved in the T3SS1-mediated cytotoxicity toward HeLa cells, did not have an ortholog in the T3SS gene cluster of the V. alginolyticus strain ZJ51 (Zhao et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Genomic DNA was extracted from the strain HN897 using the CTAB method with minor modification ( Liu et al, 2017 ). The concentration, quality and integrity of the DNA samples were evaluated using a NanoDrop 2000 Spectrophotometer (Thermo Scientific, United States) and a Bioanalyzer 2100 (Agilent Technologies, United States), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the results were corrected through pilon V1.22 software, and the final sequence was spliced to obtain the complete sequence [19,20]. The functional sequence analysis, sub-system analysis, subcellular localization analysis and functional annotation of the protein-encoding genes were performed based on the obtained complete sequence according to the previously reported method [21].…”
Section: Basic Biological Characteristics Of K Variicola Gn02mentioning
confidence: 99%